Estimating Brand Switch Among Telkomsel, Indosat, and XL Customers in Twitter Data by Using Text Mining Method - Moniaga, Steven; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2014)
Abstract. Telecommunication industry needs to retain its customers because the cost for recruit new customer is higher than to retain customers. Therefore, telecommunication industry needs to estimate its customer churn.Indonesian telecommunication industry is characterized by the dominance of prepaid market and estimating customer churn in prepaid market is more difficult because the limited customer data. On the other hand, Indonesian people tend to express their opinion through social media such as Twitter. Because of that, Twitter can be a tool to gather customer information.However, the data gathered from Twitter is text data which is difficult to be processed by the computer. Text mining method is used to extract information from text data. Text mining is analysis of text which is done by the help of computer.With text mining methods, of the many complaints from consumers can count the number of customers who switch brands. This proves that the method of text mining can be used as a new method to get information from text data contained in social media. This research will try to apply a text mining method for estimating the customer loss among Telkomsel, XL, and Indosat.